Physical Activity and Sedentary Behavior in Preterm-Born 7-Year Old Children. - John Lowe; W John Watkins; Sarah J Kotecha; Sailesh Kotecha (PLoS ONE)
Background Previous studies of preterm-born children (<37 weeks' gestation) have demonstrated decrements in lung function, exercise capacity, and increased respiratory symptoms compared to their term-born peers. However, it is unclear if these children have decreased levels of physical activity (PA) and increased sedentary behavior as a consequence of this increased respiratory morbidity. We therefore compared objectively measured PA in 7-year old preterm-born children with those born at term. Methods Children in the Millennium Cohort Study underwent assessment of PA at 7 years of age using accelerometry. 6422/12781 (50%) provided valid accelerometry and had gestational age data. A series of general linear models adjusted for confounders investigated the association between gestational age and levels of Total PA (average accelerometer counts per minute over the period of the recording), Moderate-to-Vigorous PA (MVPA) and sedentary behavior. Mediation analysis was performed to specifically investigate whether the observed association of gestational age on PA was mediated by respiratory symptoms. Results PA data were available for 79, 119, 275 and 5949 children born at 25-32, 33-34, 35-36 and 37-43 weeks' gestation respectively. Boys born at ≤32 weeks' gestation had modest but statistically significant reductions in MVPA when compared to term controls. This equated to a reduction of 9 minutes per day. No differences were found for Total PA or sedentary behavior. The association between gestational age and MVPA was not mediated by respiratory symptoms. In females, there was no association between gestational age and any measure of PA or sedentary behavior. Conclusions Boys born at ≤32 weeks' gestation took part in less MVPA than their term-born peers at 7 years of age. The differences were modest, but equated to a reduction of over 1 hour per week. Since PA levels have been shown to decline during childhood and adolescence, this vulnerable group deserves further surveillance.